1998
DOI: 10.1128/jvi.72.3.2289-2296.1998
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Overexpression of a Toxic Protein by an Adenovirus Vector with a Tetracycline-Regulatable Expression Cassette

Abstract: We have constructed two new adenovirus expression cassettes that expand both the range of genes which can be expressed with adenovirus vectors (AdV) and the range of cells in which high-level expression can be attained. By inclusion of a tetracycline-regulated promoter in the transfer vector pAdTR5, it is now possible to generate recombinant adenoviruses expressing proteins that are either cytotoxic or that interfere with adenovirus replication. We have used this strategy to generate a recombinant adenovirus e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 38 publications
1
70
0
Order By: Relevance
“…While we have demonstrated that direct injection (9) or retrograde perfusion of the salivary gland resulted in the induction of a protective immune response using an attenuated (tcMCMV) viral system, to be generally applicable as a site for vaccination, it was necessary to demonstrate that direct protein expression in the salivary gland such as that delivered via a noninfectious, conventional subunit vaccine, could also elicit effective and functionally protective immunity. Recombinant adenoviruses are a versatile tool for gene delivery and expression, since they are able to infect a broad range of cell types, and infection is not dependent on active host cell division (31,32). The most commonly used adenoviral vectors are typically devoid of E1 and E3 genes, which not only render the virus incapable of replication but also make room for the insertion of up to 7.5 kb of foreign DNA (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…While we have demonstrated that direct injection (9) or retrograde perfusion of the salivary gland resulted in the induction of a protective immune response using an attenuated (tcMCMV) viral system, to be generally applicable as a site for vaccination, it was necessary to demonstrate that direct protein expression in the salivary gland such as that delivered via a noninfectious, conventional subunit vaccine, could also elicit effective and functionally protective immunity. Recombinant adenoviruses are a versatile tool for gene delivery and expression, since they are able to infect a broad range of cell types, and infection is not dependent on active host cell division (31,32). The most commonly used adenoviral vectors are typically devoid of E1 and E3 genes, which not only render the virus incapable of replication but also make room for the insertion of up to 7.5 kb of foreign DNA (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have previously described the use of a replication deficient adenovirus in combination with adenovirus production cells (HEK293) with the aim to produce recombinant protein (Andersen and Krummen, 2002;Cô té et al, 1998;Garnier et al, 1994;Lamarche et al, 1990;Massie et al, 1995Massie et al, , 1998. In these studies, the E1-deleted vector was allowed to replicate in HEK293 cells, in the process yielding high amounts (4-20% total cell protein) of the protein of interest.…”
Section: Discussionmentioning
confidence: 99%
“…High-level recombinant protein production using AdVs was shown to be possible by using cells other than CHO cells (29,31,41,42). The cells used were either permissive for the replication of AdVs, such as 293 cells, or were non-permissive, such as HeLa, A549, or KB cells.…”
Section: Discussionmentioning
confidence: 99%
“…This plasmid contains also the 9.4-15.5 map unit segment of Ad5 genome for homologous recombination with Ad5-∆PS (see below). A plasmid (pMPG-BFP/CMV-cTA/tk-neo) expressing the cTA and the blue fluorescent protein (BFP) regulated by the CMV5 promoter (29,31) was constructed by replacing the IgG heavy and light chains of pMPG/chB43_TK/neo (32) with the cTA coding sequence excised from pAdCMV5-cTA (28) and the gene for BFP (29).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation